Penerapan Algoritma Naïve Bayes Untuk Analisis Kepuasan Penggunaan Aplikasi Bank - Domi Sepri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The world of banking has been transformed by using mobile-based applications in services and providing convenience to consumers. Android-based applications such as mobile banking are not yet fully attractive to users because of their security value. In the field of text mining, there is a method of analyzing user satisfaction through content sentiment analysis. The approach used by the author in this study is to use the Naïve Bayes Algorithm. This research was processed with the python programming language where there is a textblob module for the process of analyzing the effectiveness of using the Naïve Bayes Algorithm. From the results of the processing of this research, the accuracy of using the Naïve Bayes Algorithm is 0.8714 (87%)